IP multicast channels EXPRESS support for large-scale single-source applications. - Holbrook, Hugh W. (Computer communication review.)
In the IP multicast model, a set of hosts can be aggregated into a group of hosts with one address, to which any host can send. However, Internet TV, distance learning, file distribution and other emerging large-scale multicast applications strain the current realization of this model, which lacks a basis for charging, lacks access control, and is difficult to scale.This paper proposes an extension to IP multicast to support the channel model of multicast and describes a specific realization called EXPlicitly REquested Single-Source (EXPRESS) multicast. In this model, a multicast channel has exactly one explicitly designated source, and zero or more channel subscribers. A single protocol supports both channel subscription and efficient collection of channel information such as subscriber count. We argue that EXPRESS addresses the aforementioned problems, justifying this multicast service model in the Internet.